Je-chun-jun induced apoptosis of human cervical carcinoma HeLa cells - CHAE Han-jung; PARK Kyung-mi; LEE Geun-youn; JEONG Gi-seup; PARK Hyung-rae; KIM Hyung-min; CHAE Soo-wan; YOO Shim-keun; KIM Hyung-ryong (Acta Pharmacologica Sinica; Vol 25, No 10 (October 2004): Acta Pharmacologica Sinica, 2016)
AIM: To study the mechanism of je-chun-jun (JCJ)-inducing the apoptosis of the human cervical carcinoma, HeLa cells. METHODS: The cell viability was assessed using MTT assay. The optical density was measured at 570 nm. The caspase activity was measured using 50 mmol/L of fluorogenic substrate, AC-DEVD-AMC (caspase-3), AC-VEID-AMC (caspase-8) or AC-LEHD-AFC (caspase-9). To confirm the expression of proteins, Western blotting was performed. To detect the characteristic of apoptosis chromatin condensation, HeLa cells were stained with Hoechst 33258 in the presence of JCJ. For the cell cycle analysis, HeLa cells were incubated with Propidium iodide (PI) solution. Fluorescence intensity of cell cycle was measured using flow cytometry system. RESULTS: The loss of viability occurred following the exposure of 10 g/L JCJ. Cells treated with 10 g/L JCJ for 3 d exhibited the apoptotic morphology (brightly blue-fluorescent condensed nuclei by Hoechst 33258-staining) and the reduction of cell volume. Cells incubated with JCJ for 48 h were arrested at the G1 phase of cell cycle and their G1 checkpoint related gene products such as cyclin D1 were transiently decreased. We showed that JCJ induced the p38 MAPK activation in HeLa cells. The p38 MAPK inhibitor, SB203580 protected Hela cells from the JCJ-induced death as well as intervened the JCJ-induced accumulation of cells at the G1 phase. In contrast, MEK1 (-ERK upstream) inhibitor, PD98059 had no effect on HeLa cells. CONCLUSION: JCJ induced cell cycle arrest and apoptosis of HeLa cells through p38 MAPK pathway.